2014
DOI: 10.1590/0104-1169.3492.2453
|View full text |Cite
|
Sign up to set email alerts
|

Pain intensity, disability and depression in individuals with chronic back pain

Abstract: OBJECTIVES: to measure the pain intensity, identify the disability and depression levels in people with chronic back pain and to correlate these variables. A cross-sectional, descriptive and exploratory study was undertaken at the Pain Treatment Clinic of the University of São Paulo at Ribeirão Preto Hospital das Clínicas, between February and June 2012, after receiving approval from the Ethics Committee at the University of São Paulo at Ribeirão Preto College of Nursing. METHOD: sixty subjects with chronic ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
34
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(45 citation statements)
references
References 18 publications
8
34
0
3
Order By: Relevance
“…It was observed in the present study that 74 patients with chronic lower-back pain who vis-ited orthopedic, out-patients department suffered from MDD on the basis of DSM-5 diagnostic criteria. Many previous studies have shown depression to be prevalent among people with chronic back pain [4,5,7,16,19,20]. In clinical samples of previous studies rates of major depression in such patients ranged from 30% to 62.8 %, which is significantly higher than the rate found in the general population [21,22].…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…It was observed in the present study that 74 patients with chronic lower-back pain who vis-ited orthopedic, out-patients department suffered from MDD on the basis of DSM-5 diagnostic criteria. Many previous studies have shown depression to be prevalent among people with chronic back pain [4,5,7,16,19,20]. In clinical samples of previous studies rates of major depression in such patients ranged from 30% to 62.8 %, which is significantly higher than the rate found in the general population [21,22].…”
Section: Discussionmentioning
confidence: 93%
“…Psychological factors are important in people with chronic low back pain. Research has indicated that depression and chronic low back pain could be interrelated [5][6][7][8][9]. Major depressive disorder is a mood disorder that is characterized by depressed mood for most of the day ,nearly every day, as indicated either by a subjective report or by observation and/or loss of interest in a previously pleasurable activity, that have been present during the same 2 week period, but there might be other symptoms as well [10].…”
Section: Introductionmentioning
confidence: 99%
“…Images are more precise in detecting females than males with CH. This could be due to several biases related to pain reporting as mentioned above [45,46]. Overall, the images depicting headache pain have a low influence in detecting a cluster headache.…”
Section: Images Depicting Headache Painmentioning
confidence: 96%
“…In a stressful situation, recall of pain intensity is exaggerated and also chronic pain is itself associated with an overestimation of pain intensity [45]. Additionally, associated psychiatric co-morbidities could have an influence on how pain is reported [46]. The self-report of physical pain can be subjected to recollection bias [45,47].…”
Section: Clinical Indicators Of Ch Versus Migrainementioning
confidence: 99%
“…With regard to types of pain, the research contents of 1,114 papers were about the comorbidity of LBP and disability. This was the research hotspots that people with LBP had possibilities to get disability, pain, depression and low quality of life (33). A significant increase on articles concerning the top 20 subject categories and top 10 types of pain was noted.…”
Section: Citation Data and Research Focusesmentioning
confidence: 99%